The Nation-State Foundations of Constitutional Compliance - Peter Grajzl; Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2023)
We bring attention to a previously overlooked determinant of de jure-de facto constitutional gaps: a polity's transition to a nation-state. We argue that nation-statehood, predicated on the formation of a strong sense of national identity, lowers the government's incentive to violate constitutional provisions. To test our theory, we use a recently released longitudinal database on constitutional compliance and exploit variation in the timing of countries' attainment of nation-statehood. Our empirical findings substantiate our hypothesis. Based on our preferred estimation approach, nation-statehood bolsters both overall constitutional compliance and constitutional compliance within the subdomains of basic rights, civil rights, and property rights & the rule of law. The estimated long-run effects of nation-statehood on constitutional compliance are considerable in size. Our analysis, thus, illuminates the foundational role of nation-statehood in fostering constitutional compliance.
Keywords: D02; D72; K10; K42; P51; Z13; 330; constitutional compliance; de jure-de facto gap; nation-state; national identity; statehood